(untitled) (Polish Yearbook of International Law, 2024)
This article explores the genesis of Russian aggression against Ukraine, tracing its origins from the unprovoked illegal invasion initiated in February 2014 to the full-scale invasion in 2022. Despite initial international responses, the lack of significant sanctions against Russia or efforts to prosecute its leaders for the crime of aggression persisted until the 2022 invasion. The international community’s condemnation of the brutality accompanying this invasion underscored the need for accountability mechanisms within the existing international legal framework. However, limitations in prosecuting aggression within the International Criminal Court, coupled with challenges in amending the Rome Statute, have led to proposals for an ad hoc mechanism to address aggression gaining traction. These proposals highlight the urgency of holding aggressors accountable and safeguarding victims’ rights. Concurrently, Ukrainian jurisdiction incorporates the concept of the crime of aggression in its Criminal Code but lacks clarity on essential elements necessary for prosecuting such crimes, including the leadership element. An analysis of court verdicts reveals discrepancies in interpreting the crime of aggression, emphasising the necessity of adopting a unified approach that is consistent with international law. The article underscores the critical importance of enhancing legal frameworks, building capacity and encouraging international cooperation to ensure accountability for the crime of aggression and to preserve the rule of law.